Desmoglein 2–Dependent Arrhythmogenic Cardiomyopathy Is Caused by a Loss of Adhesive Function. (August 2015) - Kant, Sebastian; Holthöfer, Bastian; Magin, Thomas M.; Krusche, Claudia A.; Leube, Rudolf E.
<x xml:space="preserve">Abstract</x> Background— The desmosomal cadherin desmoglein 2 (Dsg2) localizes to the intercalated disc coupling adjacent cardiomyocytes. Desmoglein 2 gene (DSG2) mutations cause arrhythmogenic cardiomyopathy (AC) in human and transgenic mice. AC is characterized by arrhythmia, cardiodilation, cardiomyocyte necrosis with replacement fibrosis, interstitial fibrosis, and intercalated disc dissociation. The genetic DSG2 constellations encountered are compatible with loss of adhesion and altered signaling. To further elucidate pathomechanisms, we examined whether heart-specific Dsg2 depletion triggers cardiomyopathy. Methods and Results— Because DSG2 knockouts die during early embryogenesis, mice were prepared with cardiomyocyte-specific DSG2 ablation. Healthy transgenic animals were born with a functional heart presenting intercalated discs with incorporated desmosomal proteins. Dsg2 protein expression was reduced below 3% in the heart. All animals developed AC during postnatal growth with pronounced chamber dilation, calcifying cardiomyocyte necrosis, aseptic inflammation, interstitial and focal replacement fibrosis, and conduction defects with altered connexin 43 distribution. Electron microscopy revealed absence of desmosome-like structures and regional loss of intercalated disc adhesion. Mice carrying 2 mutant DSG2 alleles coding for Dsg2 lacking part of the adhesive EC1-EC2 domains present an indistinguishable phenotype, which is similar to that observed in human AC patients. Conclusions— The observations show that the presence of Dsg2 is not essential for late heart morphogenesis and for cardiac contractility to support postnatal life. On increasing mechanical demands, heart function is severely compromised as evidenced by the onset of cardiomyopathy with pronounced morphological alterations. We propose that loss of Dsg2 compromises adhesion, and that this is a major pathogenic mechanism in DSG2-related and probably other desmosome-related ACs.